2009
DOI: 10.1002/uog.7347
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the myocardial performance index and aortic isthmus blood flow index to predicting mortality in preterm growth‐restricted fetuses

Abstract: Objectives To evaluate the predictive value for perinatal death of the myocardial performance index (MPI) and aortic isthmus flow index (IFI), as isolated parameters and in a combined model including currently used Doppler indices, in preterm growth restricted (IUGR) fetuses. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 37 publications
8
88
1
6
Order By: Relevance
“…Absent or reversed flow during atrial contraction heralds fetal death by about 7 days, approximately 4 days earlier than methods based on biophysical profile score 10,11 . Since, as shown in this study, DV-PI and MPI progress in parallel, it is not surprising that previous studies have demonstrated that while MPI may improve the prediction of fetal death, its added value is modest when combined with DV flow 34 . We and others have previously reported that in IUGR fetuses AoI flow becomes abnormal on average 1 week earlier than does DV flow 16,17 , which may help to explain its reported poor short-term use in the prediction of fetal death 34 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Absent or reversed flow during atrial contraction heralds fetal death by about 7 days, approximately 4 days earlier than methods based on biophysical profile score 10,11 . Since, as shown in this study, DV-PI and MPI progress in parallel, it is not surprising that previous studies have demonstrated that while MPI may improve the prediction of fetal death, its added value is modest when combined with DV flow 34 . We and others have previously reported that in IUGR fetuses AoI flow becomes abnormal on average 1 week earlier than does DV flow 16,17 , which may help to explain its reported poor short-term use in the prediction of fetal death 34 .…”
Section: Discussionsupporting
confidence: 56%
“…Since, as shown in this study, DV-PI and MPI progress in parallel, it is not surprising that previous studies have demonstrated that while MPI may improve the prediction of fetal death, its added value is modest when combined with DV flow 34 . We and others have previously reported that in IUGR fetuses AoI flow becomes abnormal on average 1 week earlier than does DV flow 16,17 , which may help to explain its reported poor short-term use in the prediction of fetal death 34 . However, AoI flow has shown a strong association with neurological outcome 15 .…”
Section: Discussionsupporting
confidence: 56%
“…In addition, Figueras et al observed that abnormal alteration in aortic isthmus blood flow occurs 1 week prior than does that in ductus venosus among preterm growth restricted fetuses. Doppler evidence of retrograde flow in the aortic isthmus also found to be strongly correlated with adverse perinatal outcome in IUGR complicated pregnancies as explored in the study observed by Figueras et al [6][7][8][9][10]. The study conducted by Hernandez-Andrade et al at Spain reported 22% of perinatal death among IUGR subjects which showed significant prediction with predetermined myocardial performance index as well as prolonged NICU stay [6].…”
Section: Discussionmentioning
confidence: 91%
“…The myocardial performance index (MPI) is a novel method in fetal medicine that assesses both systolic and diastolic functions by including the measurement of isovolumetric and ejection times and would be useful in assessing the progressive hemodynamic deterioration. It has been recently reported to be independently associated with perinatal mortality, mainly in very pre-term IUGR fetuses, 101 although its role as a surveillance tool needs to be further elucidated.…”
Section: Other Cardiac Doppler Parametersmentioning
confidence: 99%